Knowledge of and Attitude Towards Epilepsy Among Women in Ile-Ife, Nigeria - Funmito O. Fehintola; Samuel A. Olowookere; Caleb A. Adegbenro; Temitope O. Afolabi; Victor Oladapo; Akinyele O. Oladimeji; Opeyemi E. Oladipo; Olayinka R. Olagunju; Ademola A. Olajide (Sudan Journal of Medical Sciences)
Background: Epilepsy is a non-contagious chronic disease with sufferers experiencing embarrassments amidst other challenges. Family caregivers are mainly women with some of them suffering from the disease. This study assessed the knowledge and attitude of women residents in an urban community towards epilepsy.